Inflation-Unemployment Trade-Offs In ASEAN-10 - Nurul Lisani; Raja Masbar; Vivi Silvia (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This study empirically explores the nature of inflation-unemployment dynamic causal relationships both in the short and long-run in the ASEAN-10 over the 1989-2018 period. Based on the panel cointegration test, the study documented a long-run equilibrium between inflation and unemployment. Using the Vector Error Correction Model (VECM) analysis, the study found an insignificant inflation-unemployment relationship in the short-run. However, in the long-run, inflation is found to affect the unemployment rate positively. Our results from the Variance Decompositions (VDCs) analysis also supported these findings, where the unemployment responded at the more significant percentage to shocks in inflation compared to the response of inflation to shocks in unemployment. These findings only supported the relevance of the Phillips curve theory in the long-run. Overall, these findings imply that although inflation targeting policy is not relevant to the short-run, it becomes crucial and effective to reduce the unemployment rate in ASEAN-10 in the long-run.JEL Classifications: E52, E58, J64 How to Cite:Lisani, N., Masbar, R., & Silvia, V. (2020). Inflation-Unemployment Trade-Offs In Asean-10. Signifikan: Jurnal Ilmu Ekonomi, 9(2), 241-256. https://doi.org/10.15408/sjie.v9i2.16346.